Critical Thinking of Female Students in Solving Mathematical Problems - Riny Arviana; Sufyani Prabawanto (Jurnal Studi Guru dan Pembelajaran, 2019)
Higher order thinking skill is a topic which attracts more attention of researchers in education field. Critical thinking belongs to higher order thinking skills. This kind of thinking should be had by everyone. Critical thinking belongs to 21st century skills Solving real world-mathematical problem regularly is assumed as one of ways encouraging one to grow and to enhance his critical thinking. A person who has good critical thinking skill in solving mathematical problems is considered to also think critically well in living his daily life. This study aims to investigate the critical thinking skill of female students consisting of ability in giving argument, drawing conclusion, and evaluating conclusion. A case study was carried out to four female students who were recruited based on their volunteering. Their critical thinking skills were evaluated by using essay test and interview. Participants’ critical thinking in solving mathematical problems is classified into high, medium, or low level. FS-1 and FS-4 are classified as low-level critical thinker. FS-2 and FS-3 are classified as high-level critical thinker. It is recommended to conduct similar study with larger sample involving both male and female students to compare their critical thinking in solving mathematical problems.